Effect of extender storage on post-thaw quality of sexed Bali bull semen verified by duplex PCR - YENDRALIZA YENDRALIZA; MUHAMAD RODIALLAH; JASWANDI JASWANDI; KHAIRUL AKMAL (Asian Journal of Agriculture, 2026)
Abstract. Yendraliza, Rodiallah M, Jaswandi, Akmal K. 2026. Effect of extender storage on post-thaw quality of sexed Bali bull semen verified by duplex PCR. Asian J Agric 10 (2): g100204. https://doi.org/10.13057/asianjagric/g100204. The application of sperm sexing technology in cattle breeding is often limited by reduced sperm quality due to processing and storage conditions. This study evaluated the effect of extender storage duration on post-thaw sperm quality and the stability of X- and Y-bearing spermatozoa in Bali cattle (Bos javanicus) using the Bovine Serum Albumin (BSA) column method. Fresh semen with acceptable initial quality was subjected to sperm sexing. The extender was stored for 0, 1, and 2 days before use. Post-thaw sperm quality was assessed based on motility, viability, plasma membrane integrity, acrosome integrity, and abnormalities. Molecular verification was performed using duplex Polymerase Chain Reaction (PCR), targeting the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and sex-determining region Y (SRY) genes. Data were analyzed using analysis of variance and regression models. Extender storage duration significantly affected plasma membrane integrity, viability, and motility (p < 0.05). Both sperm fractions showed decreased membrane integrity with increasing storage duration. Viability declined more in X-bearing spermatozoa, whereas motility decreased more in Y-bearing spermatozoa. In contrast, acrosome integrity and sperm morphology remained stable (p > 0.05). Regression analysis indicated negative trends, although moderate R² values suggest that storage duration contributed partially to sperm quality variation. Duplex PCR confirmed successful sperm separation through detection of the SRY gene exclusively in the Y-bearing fraction. In conclusion, extender storage for up to two days induces moderate changes in sperm quality without critical deterioration. These findings support the practical use of short-term extender storage in sperm sexing. Further studies integrating fertility trials and quantitative assessment of sexing accuracy are required to validate the reproductive performance of the processed semen under field conditions.